INVESTIGATION OF THE GENETIC ARCHITECTURE OF CARDIOMETABOLIC DISEASE - Gao, Chuan (Wake Forest University, 2017)
Cardiometabolic syndrome (CMS) is a clustering of interrelated risk factors (central obesity, hyperglycemia, hypertension, insulin resistance, and dyslipoproteinemia) that promotes the development of atherosclerotic vascular disease and type 2 diabetes. It was recognized as a disease entity by the American Society of Endocrinology, National Cholesterol Education Program (NCEP), and World Health Organization in 2003 (Castro, El-Atat, McFarlane, Aneja, & Sowers, 2003). Previous genetic studies with monozygotic and dizygotic twin pairs suggested a strongly heritable pattern for CMS risk factors, i.e. it is estimated that circulating lipid heritability ranges from 0.58 to 0.66 (h2HDL=0.61, h2LDL=0.59, h2TC=0.58, h2TG=0.66) (Knoblauch et al., 1997). However, the exact genetic mechanism of the disease is poorly understood.
Keywords: Cardiometabolic syndrome; Genetics; GWAS; Mexican Americans